Facultative crassulacean acid metabolism in a C3–C4 intermediate. (1st March 2019) - Winter, Klaus; Sage, Rowan F; Edwards, Erika J; Virgo, Aurelio; Holtum, Joseph A M
Abstract : Portulaca cryptopetala is a C3 –C4 intermediate species that exhibits facultative CAM suggesting that in Portulaca facultative CAM is ancestral to C4 . Abstract: The Portulacaceae enable the study of the evolutionary relationship between C4 and crassulacean acid metabolism (CAM) photosynthesis. Shoots of well-watered plants of the C3 –C4 intermediate species Portulaca cryptopetala Speg. exhibit net uptake of CO2 solely during the light. CO2 fixation is primarily via the C3 pathway as indicated by a strong stimulation of CO2 uptake when shoots were provided with air containing 2% O2 . When plants were subjected to water stress, daytime CO2 uptake was reduced and CAM-type net CO2 uptake in the dark occurred. This was accompanied by nocturnal accumulation of acid in both leaves and stems, also a defining characteristic of CAM. Following rewatering, net CO2 uptake in the dark ceased in shoots, as did nocturnal acidification of the leaves and stems. With this unequivocal demonstration of stress-related reversible, i.e. facultative, induction of CAM, P. cryptopetala becomes the first C3 –C4 intermediate species reported to exhibit CAM. Portulaca molokiniensis Hobdy, a C4 species, also exhibited CAM only when subjected to water stress. Facultative CAM has now been demonstrated in all investigated species of Portulaca, which are well sampled from across the phylogeny. This strongly suggests that in Portulaca, a lineage in which species engage predominately in C4 photosynthesis, facultative CAM is ancestral to C4 . In a broader context, it has now been demonstrated that CAM can co-exist in leaves that exhibit any of the other types of photosynthesis known in terrestrial plants: C3, C4 and C3 –C4 intermediate.